Vertigo and dizziness due to vertebrobasilar TIA: a prospective study - Neto, Arlindo C. Lima; Kim, Ji-Soo; Bernardo, Wanderley Marques; Bittar, Roseli Saraiva Moreira (Frontiers in Stroke, 2024)
Purpose: Prospectives studies on vascular vertigo and dizziness (VVD) due to vertebrobasilar TIA (VBTIA) have been sparse. This study aimed to characterize the clinical features, response to treatments, and prognostic factors of VVD due to VBTIA using a cohort established in 2021. Methods: We recruited 103 patients (58 women, 56.3%) with a mean age of 70.9± 9.3 years (range = 37 85) between January 2021 and January 2024. All patients met the diagnostic criteria of "Probable transient VVD" published by the Barany Society. The mean interval from the symptom onset to recruitment was 11.8 months (range = 0.5 72). Treatments followed the current Guidelines for Prevention of Stroke in Patients with Stroke and TIA (AHA-ASA).Patients with recurrent strokes among TIAs, and patients who were already taking an antithrombotic agent and should maintain the same regimen were excluded. Results: Imbalance (46.7%) and vertigo (39.8%) were the most frequent symptoms. The duration of attacks was < 1 minute in 35 (33.9%), 1-10 minutes in 34 (33.0%), 10-60 minutes in 15 (14.6%), and > 60 minutes in 19 (18.5%) patients. Trigger factors were reported in 20 (19.4%) patients, which included eccentric neck position in 12 (11.7%), physical exercise in 4 (3.9%), positional changes in 3 (2.9%), and eccentric neck position plus physical exercise in the remaining one (0.9%). The frequency of attacks before the medication was single or less than 1/month in 32 (31.0%), 1-4/month in 44 (42.7%), 4-8/month in 21 (20.4%), and daily in 6 (5.9%) patients. The treatment regimens were aspirin in 57 (55.3%), clopidogrel in 19 (18.5%), aspirin+clopidogrel in 25 (24.3%), and rivaroxaban in 2 (1.9%) patients. The attacks were reduced by 93.2% (IC 95%, 88.34, during the median follow-up of 12 months (range = 2 36). Only 7 (6.8%) patients experienced a new attack with the medication. No prognostic factors could be identified for the recurrences. Conclusion: VVD due to VBTIA has a broad clinical spectrum. The secondary stroke prevention is effective in VVD due to VBTIA even though no prognostic factors could be identified for the recurrences of the symptoms.